Hubungan Game Online dengan Kualitas Tidur dan Sosialisasi pada Anak Sekolah - Ririnisahawaitun; Apriani Susmita Sari; Hikmah Lia Basuni; Ahyar Rosidi (STIKes Hamzar, 2024)
Online games are one of the technological developments that are popular in student. Playing online games causes addiction so they don't care about the time spent playing which causes the quality of their sleep to be disturbed. Children with poor sleep quality will have an impact on growth, development, psychology, and concentration problems. Addiction to playing online games also has a bad impact on social interactions. Children have egocentric traits, aggressive behavior, apathy, and have bad behavior. The purpose of this study is to determine the relationship between online games and sleep quality and socialization in student at SDN 5 Mamben Daya East Lombok. This study is a correlational research with cross sectional approach. The sample was 50 boys, namely students in grades IV, V, and VI which were determined using total sampling. Children's sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while online gaming habits and socialization were measured by questionnaires adopted from other studies that have been tested for validity and reliability. Based on the chi-square test, the results was a relationship between online games and sleep quality (p value 0.001) and there was a relationship between online games and children's socialization (p value 0.000)